Cultivation of Microalgae Mixed Culture from Mahoni Small Lake UI Campus Depok using Zeolite Substrate with Varying Pb Concentration - Mutmainah, Sri; Prihantini, Nining Betawati (Jurnal Penelitian Pendidikan IPA, 2024)
Research on the cultivation of mixed cultures of Situ (small lake) Mahoni UI Campus Depok has been done. This research was a preliminary study to measure and compare the growth of Situ Mahoni mixed cultures microalgae grown in Bold's Basal Medium (BBM) with addition of zeolite and without addition of zeolite, and varying concentrations of heavy metal Pb. The concentrations of heavy metal Pb used were 0 ppm, 20 ppm, 40 ppm, 60 ppm, 80 ppm, and 100 ppm for two treatments. The results of this research were that the growth of mixed cultures with the addition of zeolite had the highest abundance of 8.800 cells/mL on day 5 (T5) at a Pb concentration of 40 ppm. Meanwhile, the growth of mixed culture without the addition of zeolite had the highest abundance of 21.700 cells/mL on day 10 (T10) at a Pb concentration of 60 ppm. The growth of microalgae mixed cultures in the medium without addition of zeolite was higher than using zeolite. The activation of zeolite pores causes the microalgae growth is relatively lower. This work aimed to study the growth of a mixed cultures microalgae in varying concentrations of Pb with and without the addition of zeolite